I need the order of the steps from beginning to end
Do you know how to solve it?
I have a general idea of how to solve it I'm just not completely sure. I mostly just end up putting the steps in the wrong order
ok show me how you solve it then :) show me what order you would put the steps in.
well I'm pretty sure you have to combine the equations then distribute
hmm an easier approach would be elimination are you familiar with the method?
whats the opposite of 2?
-2(x + y = -2) 2x – 3y = -9 Step 1: Distribute the -2 -2(x + y = -2)
The question gives me a list of steps, and I'm supposed to put them in the correct order, so what I really need is someone to help me figure out the sequence of steps
Is there a way you can paste them on to this post?
yes wait a moment
a. subtract 3x+3y=-6 (obtained in step one) from 2x-3y=-9 (given) to solve for x b. substitute the value of x in the first equation (x+y=-2) to get y=1 c. The solution for the systems of equations is (-3,1) d. x=-15 e. The solution for the systems of equations is (-15,13) f. add 3x+3y=-6(obtained in step one) to 2x-3y=-9(given), and solve for x g. x=-3 h. substitute the value of x in the first equation (x+y=-2) to get y=13 i. multiply the first equation by 3: 3(x+y)=3(-2) 3X+3Y=-6
there is a total of 5 steps
O-o huh? :/ i dont get this...
we have to figure out the order of these steps
I don't know
do you agree that 3y plus -3y = 0y ?
so what we have to do is multiply everything in equation 1 by 3 to go from x + y = -2 to 3x + 3y = -6
new system of equations 3x + 3y = -6 2x – 3y = -9
so that would be the first step? multiply everything by 3?
yeah in eq 1
okay, what's next?
now you add the equations the 3y and -3y add to 0 and go away
that leaves just x to solve for
so how would I solve for x?
what do you get when you add the equations
5x equal to what?
5x = -15 ----> x = ???
you plug that x value into any equation with x & y in it, then solve for y
so after adding the two equations what is the next step? I posted the options above
give it a shot and tell me what the order would be (based off what we've done so far)
The question doesn't ask for me to solve it. It just wants me to put the steps in order
you actually do have to solve it
based on what we've done I'd say the next step would be x=-3
and then substitute the value of x in the first equation to get y=1
yes so the solution is (-3,1)